Synthesis and characterization of tetralones as intermediates for podophyllotoxin analogues - Padmavath, Kanakapura Narayanaramakrishna; Basavaraju, Yeriyuru Basavaiah; Umesha, Basavaiah (European Journal of Chemistry, 2016)
Podophyllotoxin has captured the attention of chemists all over the world for its biological activity. It was isolated from many plants of Podophyllum species such as Podophyllum emodi, Podophyllum peltatum and others. It mainly exhibits anticancer, antimitotic, antimalarial, anti-aids and other activities. Its use is restricted due to its toxicity and unfavourable solubility. It was aimed to synthesize some new heterocyclic analogues of podophyllotoxin by changing the substituents by changing lactone ring with pyrazoline ring and substituents in ring C with hydrogen and methoxy group. Chalcones were prepared by Claisen-Schmidt reaction of 1,3-methylene dioxyacetophenone with benzaldehyde and p-anisaldehyde. The reaction of chalcone with trimethylsulphoxonium iodide in presence of sodium hydride gave cyclopropyl ketone. Intramolecular cyclization reaction of cyclopropyl ketone gave tetralone intermediates of podophyllotoxin. They are obtained in good yields. The structure of all the products was confirmed by spectral data.